Parents-School Strategic Collaborations in Early Childhood School From-Home Learning During the Pandemic - Sri Nurhayati; Nur Asiyah Qudsi; Nandang Rukanda; Anggi Fitri (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study examines parents-school strategic collaboration in early childhood school-from-home learning in Sukasari District, Bandung City, during the COVID-19 pandemic. The participants in this study were ten parents of kindergarten students, one ECCE headmaster, and 3 teachers. In this study, descriptive qualitative methodology was employed. Interviews, observations, and documentation studies were data collection methods. According to the study's findings, parents-school strategic collaborations include 1) school held school-sponsored parenting programs to improve parents capacity in fulfilling their responsibilities as learning motivators for children, 2) teachers supporting parents to play and keep intensive contact with the children to make sure parents can assist childrens’ learning effectively, 3)teachers maintained good communication channels to discuss parents challenges and difficulties in assisting childrens’ learning. It can be concluded that the strategic collaborations between parents and schools in Sukasari District run smoothly and can contribute effectively to children’s learning. This research recommends a sustainable parenting program to help parents improve their parenting capacity to assist childrens’ learning at home.